The Fear-Avoidance Components Scale (FACS): Responsiveness to Functional Restoration Treatment in a Chronic Musculoskeletal Pain Disorder (CMPD) Population. Issue 12 (December 2017) - Neblett, Randy; Mayer, Tom G.; Williams, Mark J.; Asih, Sali; Cuesta-Vargas, Antonio I.; Hartzell, Meredith M.; Gatchel, Robert J.
Abstract : Objectives: To assess the clinical validity and factor structure of the Fear-Avoidance Components Scale (FACS), a new fear-avoidance measure. Materials and Methods: In this study, 426 chronic musculoskeletal pain disorder patients were admitted to a Functional Restoration Program (FRP). They were categorized into 5 FACS severity levels, from subclinical to extreme, at admission, and again at discharge. Associations with objective lifting performance and other patient-reported psychosocial measures were determined at admission and discharge, and objective work outcomes for this predominantly disabled cohort, were assessed 1 year later. Results: Those patients in the severe and extreme FACS severity groups at admission were more likely to "drop out" of treatment than those in the lower severity groups ( P =0.05). At both admission and discharge, the FACS severity groups were highly and inversely correlated with objective lifting performance and patient-reported fear-avoidance–related psychosocial variables, including kinesiophobia, pain intensity, depressive symptoms, perceived disability, perceived injustice, and insomnia ( P s<0.001). All variables showed improvement at FRP discharge. Patients in the extreme FACS severity group at discharge were less likely to return to, or retain, work 1 year later ( P ⩽0.02). A factor analysis identified a 2-factor solution. Discussion: Strong associations were found among FACS scores and other patient-reported psychosocial and objective lifting performance variables at both admission and discharge. High discharge-FACS scores were associated with worse work outcomes 1 year after discharge. The FACS seems to be a valid and clinically useful measure for predicting attendance, physical performance, distress, and relevant work outcomes in FRP treatment of chronic musculoskeletal pain disorder patients.